A phylogenomic investigation into the evolution and biological characteristics of the Beijing lineage family of principle genetic group 1 members of mycobacterium tuberculosis - Siame, Kabengele Keith (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016